Remote learning developments in postgraduate medical education in response to the COVID-19 pandemic – A BEME systematic review: BEME Guide No. 71. (4th May 2022) - Khamees, Deena; Peterson, William; Patricio, Madalena; Pawlikowska, Teresa; Commissaris, Carolyn; Austin, Andrea; Davis, Mallory; Spadafore, Maxwell; Griffith, Max; Hider, Ahmad; Pawlik, Cameron; Stojan, Jennifer; et al.
Abstract: Background: Prior reviews investigated medical education developments in response to COVID-19, identifying the pivot to remote learning as a key area for future investigation. This review synthesized online learning developments aimed at replacing previously face-to-face 'classroom' activities for postgraduate learners. Methods: Four online databases (CINAHL, Embase, PsychINFO, and PubMed) and MedEdPublish were searched through 21 December 2020. Two authors independently screened titles, abstracts and full texts, performed data extraction, and assessed risk of bias. The PICRAT technology integration framework was applied to examine how teachers integrated and learners engaged with technology. A descriptive synthesis and outcomes were reported. A thematic analysis explored limitations and lessons learned. Results: Fifty-one publications were included. Fifteen collaborations were featured, including international partnerships and national networks of program directors. Thirty-nine developments described pivots of existing educational offerings online and twelve described new developments. Most interventions included synchronous activities ( n  Fif5). Virtual engagement was promoted through chat, virtual whiteboards, polling, and breakouts. Teacher's use of technology largely replaced traditional practice. Student engagement was largely interactive. Underpinning theories were uncommon. Quality assessments revealed moderate to high risk of bias in study reporting and methodology. Forty-five developments assessed reaction; twenty-five attitudes, knowledge or skills; and two behavior. Outcomes were markedly positive. Eighteen publications reported social media or other outcomes, including reach, engagement, and participation. Limitations included loss of social interactions, lack of hands-on experiences, challenges with technology and issues with study design. Lessons learned highlighted the flexibility of online learning, as well as practical advice to optimize the online environment. Conclusions: This review offers guidance to educators attempting to optimize learning in a post-pandemic world. Future developments would benefit from leveraging collaborations, considering technology integration frameworks, underpinning developments with theory, exploring additional outcomes, and designing and reporting developments in a manner that supports replication.